Development of the Mongolian school climate inventory - Tumenbayar, Davaanyam; Amarzaya, Amartuvshin; Ganbat, Lkhagvasuren; Gendenjamts, Sandag; Tserendorj, Navchaa (Institute of Advanced Engineering and Science, 2025)
The school climate is an essential aspect of educational practices and policies. This study aims to investigate Mongolian secondary school teachers’ perceptions of school climate and develop a measurement tool. The study involved 686 randomly selected teachers, and research data were collected online from the Mongolian National Educational Evaluation Centre. Statistical analysis was conducted using SPSS-21 software. This study was conducted in three phases: item generation, a pilot study, and a main study. Firstly, 77 items were developed on a 5-point Likert scale based on a literature review. Before the main survey, a pilot test was carried out with 200 teachers from the southern province of the country. Finally, an exploratory factor analysis (EFA) with Promax rotation was used to explore the content validity of the survey. Cronbach’s alpha was applied to assess the reliability of each factor. The statistical analysis revealed a 14-factor structure based on the data. The reliability analysis results indicated that internal consistency for all factors is at an acceptable level. The study’s overall results suggest that the proposed inventory is a validated measurement tool to examine teachers’ perceptions of the school climate in Mongolian secondary schools.